Acoustic Waves in a Viscous and Rotatory Fluid; Diffraction in a Slot - Marín Antuña, José; Pardo Vega, Javier (Revista Cubana de Física, 2009)
We describe the deduction of a non-classical seventh order partial differential equation to describe small oscillations in a viscous rotating compressible fluid. Starting from the dispersion relations of plane waves in such a fluid we conclude the physical characteristics of the wave propagation in that fluid. For a particular case of ideal rotating fluids we study the diffraction of a steady-state wave in a slot in the fluid.